Alcohol control policy measures and all‐cause mortality in Lithuania: an interrupted time–series analysis. (6th April 2021) - Štelemėkas, Mindaugas; Manthey, Jakob; Badaras, Robertas; Casswell, Sally; Ferreira‐Borges, Carina; Kalėdienė, Ramunė; Lange, Shannon; Neufeld, Maria; Petkevičienė, Janina; Radišauskas, Ričardas; Room, Robin; Telksnys, Tadas; et al.
Abstract: Background and aims: Alcohol use has been identified as a major risk factor for burden of mortality and disease, particularly for countries in eastern Europe. During the past two decades, several countries in this region have implemented effective alcohol policy measures to combat this burden. The aim of the current study was to measure the association between Lithuania's alcohol control policies and adult all‐cause mortality. Design: Interrupted time–series methodology by means of general additive models. Setting: Lithuania. Participants: Adult population of Lithuania, aged 20 years and older. Measurements: Alcohol control policies were ascertained via a document review of relevant legislation materials. Policy effects were evaluated as follows: (1) slope changes in periods of legislative (non‐)activity with regard to alcohol control policy (analysis 1); (2) level changes of three interventions following recommendations of the World Health Organization (analysis 2); and (3) level changes of seven interventions judged a priori by an international panel of experts (analysis 3). Mortality was measured by sex‐stratified and total monthly age‐standardized rates of all‐cause mortality for the adult population. Findings: During the period 2001–18, effective alcohol control policy measures were implemented on several occasions, and in those years the all‐cause mortality rate declined by approximately 3.2% more than in years without such policies. In particular, the implementation of increased taxation in 2017 was associated with reduced mortality over and above the general trend for men and in total for all analyses, which amounted to 1452 deaths avoided (95% confidence interval = −166 to –2739) in the year following the implementation of the policy. Conclusions: Alcohol control policies in Lithuania appear to have reduced the overall adult all‐cause mortality over and above secular trends.